Alien: Romulus # 7 - Spaeny, Cailee; Jonsson, David; Renaux, Archie; Merced, Isabela; Fearn, Spike; Wu, Aileen ([United States] : Disney, 2024)
While scavenging the deep ends of a derelict space station, a group of young space colonizers come face to face with the most terrifying life form in the universe.
12/03/2024
new dvd 2024 winter.
Director, Fede Alvarez.
Cailee Spaeny, David Jonsson, Archie Renaux, Isabela Merced, Spike Fearn, Aileen Wu.
MPAA rating: R.
DVD.
Keywords: Science Fiction; Horror; Suspense/Thriller.; Science fiction